Intralesional Measles, Mumps, Rubella Vaccine versus Tuberculin Purified Protein Derivative Injections in the Treatment of Palmoplantar and Periungual Warts: A Double-Blind Randomized Controlled Trial - Rutnin S. (2023)
Background: Palmoplantar and periungual warts tend to be recalcitrant. Intralesional immunotherapy can provide high efficacy with additional benefit to distant warts. However, evidence on comparative effects between intralesional immunotherapy with measles, mumps, rubella vaccine (MMR) and tuberculin purified protein derivative (PPD) and roles of dermoscopy in predicting treatment outcomes in palmoplantar/periungual warts is limited. Objectives: The study aimed to compare efficacy and safety of intralesional MMR and PPD injections in treatment of palmoplantar/periungual warts and explore associations between dermoscopic findings and treatment outcomes. Methods: We conducted a double-blind randomized controlled trial involving 40 patients with palmoplantar/periungual warts who were equally assigned to receive MMR or PPD. Intralesional injection was done every 2 weeks until clearance or maximum of 5 treatments. Results: Complete resolution was higher in MMR than PPD group (90.0% vs. 80.0% in index lesion and 81.3% vs. 54.6% in distant lesions, respectively), although the differences were statistically nonsignificant. Dermoscopic findings were not significantly associated with complete resolution. Local swelling, i.e., the most common adverse event, occurred more frequently in PPD (40.0%) than MMR group (10.0%). Conclusion: This study suggests that intralesional immunotherapy with either MMR or PPD is efficacious in palmoplantar/periungual warts, with MMR showing a trend toward higher clearance and lower adverse events.